2017
DOI: 10.1038/s41598-017-16135-5
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure estimation from respiration variables

Abstract: The aim of this study was to develop and cross-validate two models to estimate total energy expenditure (TEE) based on respiration variables in healthy subjects during daily physical activities. Ninety-nine male and female subjects systematically varying in age (18–60 years) and body mass index (BMI; 17–36 kg*m−2) completed eleven aerobic activities with a portable spirometer as the criterion measure. Two models were developed using linear regression analyses with the data from 67 randomly selected subjects (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…3e, f, studies 3 and 4). Additionally, respiratory rate, which is a parameter that is included in most models of estimation of total energy expenditure based on respiratory function 33 , was not affected by escalating doses of leptin during acute fasting or in fed state ( Fig. 3d and Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…3e, f, studies 3 and 4). Additionally, respiratory rate, which is a parameter that is included in most models of estimation of total energy expenditure based on respiratory function 33 , was not affected by escalating doses of leptin during acute fasting or in fed state ( Fig. 3d and Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…TLC as an absolute measurement related to respiratory volume can be used to address the issue of respiratory and energetic demands in modern humans 44 , 45 and, potentially, in fossil hominins as well 9 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…One recent study showed that respiratory signals including respiratory volume and rate could contribute to the estimation of VO 2 during daily physical activities (Gilgen-Ammann et al 2017). In the present experiments, respiratory signals were also collected.…”
Section: Discussionmentioning
confidence: 99%